Temperature dependence of dynamic deformation in FCC metals, aluminum and invar - Chen, L; Swift, DC; Austin, RA; Florando, JN; Hawreliak, J; Lazicki, A; Saculla, MD; Eakins, D; Bernier, JV; Kumar, M (American Institute of Physics, 2017)
Laser-driven shock experiments were performed on fcc metals, aluminum and invar, at a range of initial temperatures from approximately 120-800 K to explore the effect of initial temperature on dynamic strength properties at strain rates reaching up to 107 s−1. In aluminum, velocimetry data demonstrated an increase of peak stress of the elastic wave, σE, with initial temperature. Alternatively, for invar, σE exhibits little-to-no decrease over the same initial temperature range. Aluminum’s unusual deformation behavior is found to primarily be due to anharmonic vibrational effects. Differences in the magnetic structure of aluminum and invar can account for discrepancies in high rate deformation behavior.